PENGARUH PENDIDIKAN DAN PELATIHAN KEWIRAUSAHAAN TERHADAP MINAT MASYARAKAT BERWIRAUSAHA (STUDI KASUS DI BALAI LATIHAN KERJA KABUPATEN BUNGO) - Septawati Patimah Septawati Patimah; Mayroza Wiska; Yesi Gusteti (MANAJEMEN DEWANTARA, 2022)
This study was conducted to find out the effect of entrepreneurship education and training on people's interest in entrepreneurship (a case study at the Bungo Regency Job Training Center). The purpose of this study was to find out and analyze the effect of education and job training on the public's interest in entrepreneurship. This research uses quantitative method, to collect the data used questionnaire. The data analysis technique with Validity Test, Reliability Test, Correlation Analysis, Multiple Linear Regression Analysis, Classical Assumption Test, T Test, F Test and Determination Test (R2). The population in this study were 224 respondents and 144 respondents were used as sample. The results of the study showed that partially (t test) it is proven that entrepreneurship education has a significant effect on people's interest in entrepreneurship, the entrepreneurship training has a significant effect on the people's interest in entrepreneurship, simultaneously ( test f) together with entrepreneurship education and training have a significant effect on entrepreneurship interest. The Adjusted R2 value is 0.624, which means that all independent variables can affect 62.4% of the dependent variable. While the remaining 37.6% can be influenced by other factors not tested in this study.